Professional Essays: Literature, Women and Work in late 19th century Buenos Aires Press (Anclajes, 2017)
One of the changes brought about by the modernization of Argentine culture and the emergence of a market for cultural goods in the last quarter of the 19th century is an increase in women writers and readers in the public sphere, especially in magazines dedicated to female readership. These periodicals not only offer female writers a place to collaborate and assume an authorial voice through their writings but to also actively develop models that seek to ease the tension surrounding a new figure: the woman of letters. This article seeks to analyze the different ways in which two wellknown female writers from that time, Josefina Pelliza and Lola Larrosa, take part in those magazines and negotiate with the profiles of female authorship that circulate in them to develop their budding literary careers.
Keywords: women writers; periodical press; professionalization; Argentine literature; 19th century